Cultural adaption and validation of the German version of the diagnostic thinking inventory (DTI-G) / Ein Instrument zur Erhebung diagnostischer Kompetenz: Validierung und kulturelle Adaptation des Diagnostic Thinking Inventory (DTI-G) - Schäfer Axel Georg Meender; Sebelin Britta; Spitzer Lena (Sciendo, 2019)
Diagnostic ability is essential for expert professional practice. Several instruments have been developed to assess diagnostic skills independent of specific knowledge. One such instrument is the diagnostic thinking inventory (DTI), which is used in different settings to evaluate diagnostic performance and has shown acceptable reliability and validity.